The importance of revised questionnaires for parental completion in Romanian atopic children. - Chiriac, A.E.; Pinteala, T.; Chiriac, A. (European Journal of Pediatric Dermatology, 2018)
ISAAC written and signed questionnaires by parents of children diagnosed with atopic dermatitis are worldwide used with an important role in evaluating multiple aspects of the disease. Taking into consideration geographical, epidemiological, clinical and other data specific to Romania, questionnaires addressed to parents enquiring about atopic dermatitis were realized. The aim of the questionnaire was the standardization of questions on potential risk factors for atopic disease, for comparison to western countries and to highlight the specific aspects. This questionnaire is a risk factor type questionnaire derived from ISAAC questionnaire, but strongly adapted to Romanian population. It could be a major instrument to estimate correlation of disease prevalence and risk factors between different centers and at the individual level.